2004
DOI: 10.1111/j.1365-2036.2004.02027.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary anti‐Helicobacter pylori‐urease immunoglobulin Y on Helicobacter pylori infection

Abstract: Summary Recently, chicken egg yolk was recognized as an inexpensive antibody source, and the therapeutic usefulness of egg yolk immunoglobulin Y (IgY) in oral passive immunization has been investigated. Although multiple antibiotic treatments eradicate most Helicobacter pylori (H. pylori) infections, therapy fails in 10–15% of cases due to the development of drug resistance. Consequently, it is important that new, more broadly based therapies for the treatment of H. pylori infection should be identified. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 42 publications
0
71
1
Order By: Relevance
“…[23] In this regard, oral administration of active antibodies specific to H. pylori may be advantageous in that recognition of H. pylori by the antibody, which would efficiently inhibit adhesion of the bacterium to human epithelial cells. [24] However, a stable and reliable H. pylori infection animal model would be necessary for evaluating vaccine efficacy and helpful for understanding the pathological mechanism of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…[23] In this regard, oral administration of active antibodies specific to H. pylori may be advantageous in that recognition of H. pylori by the antibody, which would efficiently inhibit adhesion of the bacterium to human epithelial cells. [24] However, a stable and reliable H. pylori infection animal model would be necessary for evaluating vaccine efficacy and helpful for understanding the pathological mechanism of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Peroral administration with IgY is an attractive approach because IgY does not activate mammalian complement or interact with mammalian Fc receptors that could mediate inflammatory response in the gastrointestinal tract. 13 In recent papers we have reported that anti-gingipain IgY had preventive effect against periodontitis in human patients.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of IgY antibodies has been tested for many years with promising results [80] to different pathogens as human rotavirus [81]; dental plaque formation by Streptococcus mutans [82,83]; enteropathogenic E. coli [84]; Helicobacter pylori [85,86]; Cryptosporidium parvum [87,88]; canine parvovirus [89]; Porphyromonas gingivalis [90]; Pseudomonas aeruginosa [91]; shrimp's white spot syndrome virus [92]; Eimeria acervulina [93]; E. tenella and E. maxima [94,95]; H5N1 e H1N1 in mice [96]; Vibrio cholerae [97]; rotavirus and norovirus [98]; Campylobacter jejuni [99][100][101]; and botulinum neurotoxins [102]. Immunotherapy as a passive immunization method to neutralize venom using purified IgY proved to be efficient for therapy protocol [103][104][105][106][107].…”
Section: Using Igy For Passive Immunizationmentioning
confidence: 99%